CULTURAL RELATIONS OF THE PEOPLES OF UZBEKISTAN AND AZERBAIJAN (ON THE EXAMPLE OF THE FIELDS OF CINEMA AND THEATER) (Scientific journal of the Fergana State University, 2023)
The article highlights the issues of the history of cultural relations of the peoples of Uzbekistan and Azerbaijan during the years, especially, cooperation in the field of cinema and theater.